Does Application-Oriented Networking Impact SOA? Use of AON will revolutionize SOA as well as the networking arena. - Majumdar, Bijoy
The requirement of being agile in today's market means having business processes at one's command that can easily be modified for different requirements. This requirement, along with usage of open standards that addresses the problem of interoperability, compels today's business units to move towards service-oriented architecture (SOA). This article talks about the impact AON would have on such business systems.